Vascular Damage in Newly Diagnosed Young Hypertensive Patients, Assessed by Carotid Intima Media Thickness: An Indian Perspective - Rohit Singla; Anoop Jain; Rishu single; Rasheed Ahmed (Journal of Hypertension and Cardiology, 2013)
Background: Western studies have shown that hypertension increases carotid intima media thickness (cIMT) as early as in childhood and adolescence. However, similar data from India is lacking. Indians have different genetic, racial, geographic, cultural and dietary patterns. Hence a similar trend may not be experienced among young Indian subjects. Methods: 46 young cases (age 16 – 35 years) of hypertension were recruited along with age, sex and BMI matched controls. Patients with body mass index (BMI) >25 kg/m2, diabetes mellitus and secondary causes of hypertension were ruled out. All patients underwent carotid ultrasonography for assessment of cIMT. Results: Mean age and BMI of cases was 25.4 years and 20.89 kg/m2 respectively. 67.4% were male. For all of the subjects combined (n=92), cIMT correlated with BMI (r = 0.244; P=0.019), office systolic blood pressure (SBP) (r = 0.556; p<0.001) and office diastolic blood pressure (DBP) (r =0.426; p<0.001). Among hypertensive subjects (n=46), there was a significant positive correlation between cIMT and SBP (r=0.611, p<0.001). In contrast to SBP, DBP correlated insignificantly with cIMT (r= 0.217; p = 0.14) in the hypertensive subjects. Conclusion: Elevated blood pressure, especially systolic, correlates with increased cIMT among young Indian hypertensives. This provides strong evidence that primary hypertension in early life also is associated with vascular pathology, independent of the effects of obesity and diabetes
Keywords: carotid intima media thickness